A facile template approach to preparing stable NFC/Ag/polyaniline nanocomposites for imparting multifunctionality to paper. (15th August 2018) - Liu, Kai; Nasrallah, Joseph; Chen, Lihui; Huang, Liulian; Ni, Yonghao; Lin, Shan; Wang, Hongping
Highlights: The NFC/Ag/polyaniline nanocomposites were prepared by a facile method. The NFC/Ag/polyaniline nanocomposites can keep stable in solution. The NFC/Ag/polyaniline nanocomposites imparted multifunctionality to paper. Abstract: Nanocomposites of function polymer and inorganic nanoparticles have many beneficial properties and can be used in many applications. However, the formation of aggregates of the polymer and inorganic nanoparticles in the nanocomposites limits their use in practical applications. Here, a facile approach to preparing stable nanofibrillated cellulose (NFC)/Ag/polyaniline nanocomposites by the templates of NFC was developed. The Ag nanoparticles and polyaniline were loaded on the NFC by the reduction of Ag cations and in situ chemical polymerization in the templates of NFC. The network structure of the NFC and the electrostatic repulsion resulted in the formation of stable nanocomposites. Owing to the well-dispersed Ag nanoparticles and polyaniline in the nanocomposites, the nanocomposites can be coated on the paper uniformly, thus imparting excellent conductivity and antibacterial properties to paper. The coated paper can be used as a new type of conductive paper with excellent antibacterial activity.